Working Capital Turnover, Sales Growth, Debt To Equity Ratio, and Current Ratio on Profitability - Hana Kurnia Saraswati; Fahrul Imam Santoso (GOVERNORS, 2026)
This study aims to examine the effect of Working Capital Turnover, Sales Growth, Debt To Equity Ratio, and Current Ratio on Profitability. The population used was 58 infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. This study employed a quantitative research method with a purposive sampling technique, a sampling technique with specific criteria. Based on these criteria, 12 companies were selected as samples. In this study, the researchers used data analysis techniques including descriptive statistical analysis, classical assumption tests, multiple linear regression tests, and hypothesis testing using SPSS version 26. The results showed that Working Capital Turnover and Sales Growth had a positive and significant effect on Profitability, Debt To Equity Ratio (DER) had a negative and significant effect on profitability, while the Current Ratio (CR) had a negative and insignificant effect on profitability. Finally, collectively, Working Capital Turnover, Sales Growth, Debt To Equity Ratio (DER), and Current Ratio (CR) had an effect on Profitability.